(untitled) (Research, Society and Development, 2021)
In this study, we evaluated the prevalence of Campylobacter jejuni, Campylobcater coli, and virulence genes in fresh, chilled, and frozen chicken carcasses with livers and gizzards sold in public markets and supermarkets. Of the 90 samples analyzed, C. jejuni was the most prevalent, with 28.8% of positive samples, whereas C. coli was positive in 15.6% of samples. In public market samples, C. coli had a higher prevalence than C. jejuni, with 16.7% positive samples detected, whereas in supermarket samples, C. jejuni was more prevalent (36.7% positivity). C. jejuni was detected in all forms of commercialized carcasses; however, there was a higher prevalence (43.3%) in chilled samples than C. coli, which was not detected in frozen samples but showed a higher prevalence (16.7%) in fresh samples. Both species were detected in different poultry products, with C. jejuni being more prevalent (53.3%) in liver samples. C. coli showed a higher prevalence in samples of meat pieces (10%). The presence of five virulence genes related to adherence (Peb1, JlpA, CadF, and CapA) and invasion (CiaB) was also observed in both species.